Exploring vocabulary learning strategy using online learning management system among TESL trainee teachers - Umazah, Omar (2023)
Vocabulary learning strategy (VLS) is a very significant process for the second language learner (L2) in acquiring wide vocabulary especially for TESL teacher trainees for their future usage. However, VLSs are not being emphasized and specified in the structure of the TESL programme at Institute of Teacher Education (ITE) of the study. So, online learning management system (LMS), Schoology becomes a major platform in exploring VLSs in this study. The study aims to (i) examine the types of VLSs used by the TESL trainee teachers; (ii) explore on how an LMS helps TESL trainee teachers in enhancing their VLSs; and (iii) investigate the issues or challenges faced by the TESL trainee teachers in using LMS. This qualitative study used multiple methods such as interviews, online postings and discussion via LMS Schoology and field notes. It involved 14 research participants in three phases within 15- week interactions. During the phases, they had to write online reflections based on the tasks given via the LMS which were analysed using CEFR Text Analyzer. The structured online interviews, field notes and face-to-face interviews were analysed thematically using ATLAS.ti Software. The findings indicated the research participants had used VLSs similarly that had been highlighted in Gu and Johnson's (1996) vocabulary learning domain, metacognitive and cognitive strategies. In this study, online and modification strategies are two strategies used by the research participants that had been explored through the LMS. This study depicts how LMS helps the TESL trainee teachers in enhancing their VLSs and presents some issues and challenges faced by the research participants. This study was significant for trainee teachers, teacher trainers, the curriculum developers, and L2 researchers. There is a need to maximize the use of LMS in increasing TESL trainee teachers’ vocabulary learning through more VLSs for successful teaching and learning process.